Using Publicly Available Building Data to Improve 3D Map - Krygiel, Krzysztof; Majek, Karol; Będkowski, Janusz (Wydawnictwo Politechniki Łódzkiej, 2023)
In this paper, we address the problem of 3D Map accuracy. No access to RTK GPS or LIDAR leads to poor accuracy of the map. High-rise buildings cause even greater trajectory errors. We used artificial intelligence methods to integrate publicly available building data and show that it can improve map accuracy from monocular camera and inaccurate GPS receiver. The main novelty is a method of building elevation detection in sparse point cloud data. We match detected elevations with building data and use modified bundle-adjustment algorithm to improve the map. We show that proposed approach decreases the trajectory error.
Keywords: SLAM; 3D map; building elevation detection; SLAM; mapa 3D; wykrywanie wysokości budynków